The Influence of The Head of Madrasah and Infrastructure Facilities on The Quality of Education Through Teacher Competence - Sutrisno, Sutrisno; Hayati, Hayati; Saputra, Nanda; Arifin, Syamsul; Kartiko, Ari (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to analyze whether teacher competence is able to mediate madrasa heads and infrastructure on the quality of education. This study uses a quantitative approach, which consists of two exogenous variables of madrasa heads and infrastructure, one endogenous variable of education quality, and an intervention variable, namely teacher competency. The data obtained is primary data obtained directly from the respondents by dividing the questionnaires among the respondents. The research instrument used a Likert scale of 1-5, while data analysis used SEM diagram analysis which was processed using Amos Structural Equation Modeling. The results of the study show that teacher competence is able to mediate madrasa heads and infrastructure on the quality of education through teacher competence. These results indicate that teacher competence is able to mediate exogenous and endogenous variables.